Electron‐Deficient Heteroacenes that Contain Two Boron Atoms: Near‐Infrared Fluorescence Based on a Push–Pull Effect. Issue 40 (20th July 2021) - Ito, Masato; Sakai, Mika; Ando, Naoki; Yamaguchi, Shigehiro
Abstract: Electron‐deficient heteroacenes that contain two tricoordinate boron atoms in their acene skeletons and planarized phenyl ether moieties at their periphery were synthesized via the borylation of silicon‐bridged precursors. X‐ray crystallographic analysis revealed quinoidal structures, which give rise to two‐step reversible redox processes for both the reduction and oxidation. These compounds exhibit intense absorption and sharp fluorescence bands with vibronic structures in the near‐infrared (NIR) region. These properties originate from the push–pull effect along the long axis of the molecule derived from the electron‐donating ether moieties and the electron‐accepting boron moieties. Of particular note is the NIR emission of the thienothiophene‐centered heteroacene, which has a maximum at 952 nm with a narrow band width of 309 cm −1 in cyclohexane. A Franck–Condon analysis revealed the crucial role of the sterically less‐hindered thienothiophene spacer in achieving this sharp emission band. Abstract : Push–pull modification of acene scaffolds by incorporation of two electron‐accepting boron atoms and two electron‐donating planarized phenyl ether moieties renders the resulting compounds near‐infrared (NIR) active. Of particular note is a thienothiophene‐centered 10‐ring‐fused diboraheteroacene that exhibits a sharp NIR emission band with a narrow band width.